PERKECAMBAHAN EMPAT JENIS Legume Cover Crop (LCC) - Agusdin Dharma Fefirenta; Sunardi Sunardi; Apriliana Dyah Prawestri (Gunung Djati Conference Series, 2023)
Cover crops, especially legume cover crop (LCC) are ground cover plants used for protecting the soil from erosion and preventing loss of nutrients, furthermore they can improve soil quality physically, chemically, and biologically. This study aimed to determine the effectiveness of soaking seeds, light exposure and media on the seed germination of four species of LCC (Calopogonium mucunoides, Centrosema pubescens, Mucuna bracteata, and Pueraria javanica). This study was conducted using a factorial Completely Randomized Design (CRD), which was divided into two experiments i.e., the effect of seed soaking and light exposure on seed germination. Based on the statistical analysis, the first experiment showed that there was no interaction between LCC species and soaking treatment. In the other experiment, the light factor only had a significant effect on the increase of sprout length, length of 14 days old sprouts, and growth of plumules. Germination media, namely paper and sand, had an effect on two types of LCC. Paper media significantly affected the germination percentage of M. bracteata as well as the vigor index and germination rate of Ce. pubescens, while the sand medium had a significant effect on the germination rate of Ce. pubescens. It can be concluded that seed germination of LCC species was not affected by add soaking treatment but was more influenced by light exposure and media in which each species showed a different germination response.